Implementation of the Culturally Responsive Teaching Approach in Learning Narrative Texts Based on Local Traditions and Islamic Values at SMP Negeri 26 Makassar - Munirah, Munirah; Sulfasyah, Sulfasyah; Rahim, Abdul Rahman; Yusuf, Akram Budiman (Universitas Muhammadiyah Malang, 2025)
This study aims to describe the implementation of the Culturally Responsive Teaching (CRT) approach in teaching narrative texts based on local traditions and Islamic values ​​at SMP Negeri 26 Makassar. The problem raised is students' lack of understanding of materials relevant to their local culture and religion, which leads to low engagement in learning. This study uses a descriptive qualitative approach with data collection techniques in the form of observation, in-depth interviews, and documentation. Data were obtained directly from one Indonesian language teacher and the eighth-grade students involved in the learning. The results show that the implementation of CRT can increase student engagement, strengthen cultural identity, and improve students' understanding of narrative texts containing local and Islamic values. Although challenges such as limited time and resources were encountered, this approach proved effective in bridging the gap between learning materials and students' cultural realities. This study provides theoretical contributions to the development of a more contextual CRT in Indonesia. It offers practical recommendations for teachers and policymakers to integrate local and religious values ​​into the education curriculum. However, this study has limitations in terms of location and time coverage, which opens opportunities for further research with a broader sample, sustainable educational tourism, enhancing community empowerment, and supporting rural development.